A Literature Review on the Role of the Sharia Supervisory Board in Maintaining Sharia Compliance in Islamic Banks - Thoib, Muhammad; Wargo; Bibi , Tahira (CV. Zabags Qu Publish, 2025)
Sharia Supervisory Boards (SSBs) play a crucial role in ensuring that Islamic banks operate in accordance with Islamic legal principles, serving as a key component of accountable and ethically grounded sharia governance. As the Islamic financial industry expands rapidly, concerns have emerged regarding the actual effectiveness of SSBs in carrying out their oversight functions. This study employs a narrative literature review approach to explore the strategic roles, challenges, and institutional effectiveness of SSBs based on a critical synthesis of peer-reviewed academic publications, regulatory reports, and other credible open-access sources published in the last decade. The findings reveal that while SSBs are formally embedded within Islamic banking structures, their practical impact often remains constrained by limited authority, structural dependency, and potential conflicts of interest. Furthermore, variations in competence, access to information, and standardization of governance practices also influence their performance. This article contributes to the academic discourse by systematically mapping the theoretical and practical dimensions of SSB functions and offering conceptual insights to strengthen sharia governance through more independent and credible oversight mechanisms aligned with the objectives of maqāṣid al-sharī‘ah.